Problems of Modernization of Curricula for Teaching "Descriptive Geometry and Engineering Graphics" in Higher Education Institutions in the Field of Architecture and Construction and Technical Education - Shukurullaevich, Suvonov Obidjon (European Journal of Life Safety and Stability (2660-9630), 2021)
This scientific article discusses the problems of modernization of curricula for teaching the subject "Descriptive Geometry and Engineering Graphics" "Strict transition to modern advanced technologies, modern production structures, complex processing of mineral resources and requires the formation of a system of industries for the production of finished products, which requires a lot of knowledge”.